Wedelolactone Enhances Osteoblastogenesis but Inhibits Osteoclastogenesis through Sema3A/NRP1/PlexinA1 Pathway - Liu, Yan-Qiu; Han, Xiao-Fei; Bo, Jun-Xia; Ma, Hui-Peng (Frontiers in Pharmacology, 2016)
Bone remodeling balance is maintained by tight coupling of osteoblast-mediated bone formation and osteoclast-mediated bone resorption. Thus, agents with the capacity to regulate osteoblastogenesis and osteoclastogenesis have been investigated for therapy of bone-related diseases such as osteoporosis. In this study, we found that wedelolactone, a compound isolated from Ecliptae Herba, and a 9-day incubation fraction of conditioned media obtained from wedelolactone-treated bone marrow mesenchymal cells (BMSC) significantly inhibited tartrate-resistant acid phosphatase (TRAP) activity in RANKL-stimulated osteoclastic RAW264.7 cells. Addition of the semaphorin 3A (Sema 3A) antibody to the conditioned media partially blocked the medium's inhibitory effects on the RAW264.7 cells. In BMSC, mRNA expression of Sema 3A increased in the presence of different wedelolactone concentrations. Blocking Sema 3A activity with its antibody reversed wedelolactone-induced alkaline phosphatase (ALP) activity in BMSC and concurrently enhanced wedelolactone-reduced TRAP activity in osteoclastic RAW264.7 cells. Moreover, in BMSC, wedelolactone enhanced binding of Sema 3A with cell-surface receptors, including neuropilin (NRP)1 and plexinA1. Furthermore, nuclear accumulation of β-catenin, a transcription factor acting downstream of wedelolactone-induced Sema 3A signaling, was blocked by the Sema 3A antibody. In osteoclastic RAW264.7 cells, conditioned media and wedelolactone promoted the formation of plexin A1-NRP1, but conditioned media also caused the sequestration of the plexin A1-DNAX-activating protein 12 (DAP12) complex and suppressed the phosphorylation of phospholipase C (PLC)γ2. These data suggest that wedelolactone promoted osteoblastogenesis through production of Sema 3A, thus inducing the formation of a Sema 3A‒plexinA1‒Nrp1 complex and β-catenin activation. In osteoclastic RAW264.7 cells, wedelolactone inhibited osteoclastogenesis through sequestration of the plexinA1‒DAP12 complex, induced the formation of plexinA1-Nrp1 complex, and suppressed PLCγ2 activation.